2019
DOI: 10.33545/surgery.2019.v3.i4b.224
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk factors for complications after pancreatic surgery

Abstract: Introduction: Mortality rates after pancreaticoduodenectomy have decreased dramatically during the last two decades in high volume centers. However, despite a low mortality rate and improvements in perioperative care, morbidity rate is still high after pancreaticoduodenectomy. Studies defining the role of potential risk factors for the development of postoperative complications are few, and sometimes with conflicting results. There is need to identify potential risk factors for predicting complications after p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Although the Whipple operation is considered one of the most challenging abdominal operations, it remains the only curative option for periampullary malignancy. 31 In this study, developing postoperative morbidity was not statistically significant in association with sex distribution (Pvalue = 0.82), which is similar to a study done in India by Prasad et al 32 Regarding age, this study showed that there is significant association between increased age and developing postoperative morbidity (P-value = 0.03), which is similar to a study done by Haigh et al 33 The presence of preoperative co-morbidities, be it hypertension, diabetes, cardiac and pulmonary diseases or a history of smoking, were associated with significant morbidity in this study (P-value = 0.0001), which is similar to a study done in India by Madhav et al 14 The site of the tumor (pancreatic, duodenal, ampullary or distal common bile duct) had no significant association with developing postoperative morbidity (P-value = 0.38), which is similar to a study done by House et al 34 Tumor differentiation was not significantly associated with postoperative morbidity (Pvalue = 0.35), in contrast to a study done by Ajith Prasad et al, where there was a significant difference in postoperative morbidity with poorly differentiated tumors. 32 Lymph nodes involvement by histopathological report was not associated with postoperative morbidity (Pvalue = 0.14), which is similar to a study done by Yeo et al 35 The most common postoperative complications in this study were pancreatic leakage (15.9%), superficial surgical site infection (13.6%) and pulmonary embolism (11.3%), which is similar to a study done by Greenblatt et al, 36 whose frequencies of the above complications were 15.3%, 13.1% and 9.5%, respectively.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Although the Whipple operation is considered one of the most challenging abdominal operations, it remains the only curative option for periampullary malignancy. 31 In this study, developing postoperative morbidity was not statistically significant in association with sex distribution (Pvalue = 0.82), which is similar to a study done in India by Prasad et al 32 Regarding age, this study showed that there is significant association between increased age and developing postoperative morbidity (P-value = 0.03), which is similar to a study done by Haigh et al 33 The presence of preoperative co-morbidities, be it hypertension, diabetes, cardiac and pulmonary diseases or a history of smoking, were associated with significant morbidity in this study (P-value = 0.0001), which is similar to a study done in India by Madhav et al 14 The site of the tumor (pancreatic, duodenal, ampullary or distal common bile duct) had no significant association with developing postoperative morbidity (P-value = 0.38), which is similar to a study done by House et al 34 Tumor differentiation was not significantly associated with postoperative morbidity (Pvalue = 0.35), in contrast to a study done by Ajith Prasad et al, where there was a significant difference in postoperative morbidity with poorly differentiated tumors. 32 Lymph nodes involvement by histopathological report was not associated with postoperative morbidity (Pvalue = 0.14), which is similar to a study done by Yeo et al 35 The most common postoperative complications in this study were pancreatic leakage (15.9%), superficial surgical site infection (13.6%) and pulmonary embolism (11.3%), which is similar to a study done by Greenblatt et al, 36 whose frequencies of the above complications were 15.3%, 13.1% and 9.5%, respectively.…”
Section: Resultssupporting
confidence: 90%
“…8 Also, despite the decrease in mortality in the last two decades, morbidity is still high. 14 The mortality rate in high volume centers (where individual surgeons perform more than 15 cases yearly) is about 5%. 15 Many important variables contribute to the outcome of this operation, based on patient's general health, experience of surgeons and the volume of complex operations done by the surgeon.…”
Section: Introductionmentioning
confidence: 99%